Delegitimization of the Constitutional Court in the Age of Artificial Intelligence: A Critical Review of the Shift from Contextual Justice to Legal Formalism - Muammar Asyraf; Rizki Ramadani (Manunggal Halim Jaya, 2026)
The rapid infiltration of Artificial Intelligence (AI) into various sectors, including the legal domain, generates a fundamental paradox between technocratic efficiency and substantive justice. This study aims to analyze the threats posed by the mechanistic logic of AI to the epistemic authority of the Constitutional Court (MK) as the guardian of the constitution. Employing a juridical-normative method with a conceptual approach, this research conducts a systematic literature study of legal, legal philosophy, and legal technology sources published between 2017 and 2025, analyzed through hermeneutic interpretation encompassing textual, conceptual, and teleological dimensions. The findings reveal two principal threats: first, AI risks shifting the paradigm of constitutional interpretation away from a dynamic and contextual living constitution approach toward rigid legal formalism anchored in historical data, thereby neglecting moral, social, and contextual dimensions; second, the dominance of algorithmic logic threatens the delegitimization of the Constitutional Court, as algorithmically influenced decisions fail to capture the complexity of societal justice and the humanistic dimension of judicial proceedings. Unlike previous studies that focus on technical aspects or general algorithmic ethics, this research introduces the conceptualization of a dichotomy between mechanistic justice and contextual justice in the specific context of Indonesia’s civil law constitutional adjudication. The study concludes that while AI serves a legitimate role as a technical tool, its logical dominance fundamentally endangers the essence of the Constitutional Court as an institution that resolves disputes through wisdom, conscience, and constitutional values. A strict regulatory framework comprising five key components is therefore proposed to ensure that AI remains a supportive instrument rather than a substitute for constitutional authority.